Evaluación de control interno a la cooperativa de ahorro y crédito Pilahuín Ltda. matriz del cantón salcedo, provincia de Cotopaxi en el período económico 2017. - Tigasi Quishpe, Ana María (2018)
The research project carried out in the Cooperativa de Ahorro y Credito Pilahuín Ltda. It was carried out with the purpose of evaluating the internal control, to know what irregularities are presented, through the information provided by the financial institution. It was able to carry out a more in-depth study, where it was possible to use research instruments such as the interview, which was applied to each of the heads of the departments that currently exist within the entity and in the same way using a method of internal control could be implemented questionnaires that helped to evaluate from different perspectives where the following components are involved, such as the control environment, risk assessment, control activities, information and communication and monitoring. In addition, thanks to this procedure it was evident that there are mostly weaknesses that affect the cooperative economically, being its main problem the ignorance of the manuals that each area has on the part of the employees being that the bosses know they do not communicate them, it is say they know the functions that the internal control has and how it would help at the moment of being applied correctly. So therefore they took into account the recommendations that were issued after the evacuation was carried out, so it will benefit the cooperative both the manager because it will be able to make correct decisions and the employees to carry out their functions in an efficient way contributing to the improvement of the financial institution.